Pengaruh Konten Tiktok @pandawaragroup Terhadap Perilaku Menjaga Kebersihan Lingkungan - Wijonarko, Dimas; Ramdhani, Muhammad; Arindawati, Weni (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The study "The Influence of @pandawaragroup Tiktok Content on Environmental Cleanliness Behavior" is motivated by content from @pandawaragroup which is quite popular among the public. With the aim of finding out how much influence @pandawaragroup's Tiktok content has on behavior in maintaining environmental cleanliness. This research uses quantitative research methods with an explanatory survey. The theory used is Uses and Effect with a population of followers of the Instagram account @pandawaragroup and sampling using a non- probability sampling technique with a purposive sampling method. The data collection technique used was a questionnaire using Google Form. Meanwhile, the data analysis technique uses a Likert scale. The results of this research are that the intensity, message content and attractiveness of the Tiktok @pandawaragroup content significantly influence the behavior of maintaining environmental cleanliness.